Network Pharmacology Analysis and Experimental Verification of Weinaian Capsule for Treating Gastric Cancer - Cheng, Qisheng; Li, Xinghua; Shen, Lujun; Yang, Ting (Current Pharmaceutical Biotechnology, 2026)
BackgroundTraditional Chinese medicine has been widely used to treat gastric cancer, but the effect of the Weinaian capsule on gastric cancer is still unclear.ObjectiveThis study aimed to find the potential therapeutic targets and pharmacological mechanisms of Weinaian capsule in gastric cancer.MethodsWe employed the network pharmacological analysis to find the therapeutic targets. Firstly, we searched the bioactive components of Weinaian capsule in TCMSP and the Swiss database. We downloaded disease gastric cancer targets from the GeneCards database and used the Venn diagram to identify common targets for disease and drugs. Then, we performed GO and KEGG pathway enrichment analyses, used the Cytoscape software to screen core targets and components, and constructed a drug-disease-target network. In addition, visual molecular docking and molecular dynamics simulation of targets and components with strong affinity were performed. Finally, we verified the effect of the drug on cell proliferation and metastasis using CCK8, clonal formation, and wound healing assays, and investigated the molecular mechanism by qRT-PCR.ResultsA total of 33 bioactive components were procured; 128 common targets for gastric cancer and drugs were screened. The GO and KEGG pathway enrichment analyses showed the PI3K-AKT pathway to be at the top. The core target AKT1 and the core component isorhamnetin exhibited the strongest molecular binding force and good binding stability. Compared to the control group, Weinaian capsule group inhibited gastric cancer cell proliferation and migration by down-regulating the expressions of PI3K and AKT.ConclusionWeinaian capsule inhibited cell proliferation and metastasis by affecting the PI3K-AKT pathway in gastric cancer.
Keywords: proliferation